Compliance Risk Management On Indonesian Taxation: Is It As Good As Expected? - Erlin Phinanti; Agustinus Lumban Tobing (Universitas Serang Raya, 2023)
This research was conducted on the revised Compliance Risk Management (CRM) of the tax administration by the Directorate General of Taxes (DJP) in 2021 through SE39/PJ/2021. DGT issued guidelines for implementing CRM-based and business intelligence-based supervisory activities. The new policy should be evaluated to find out whether the policy increases the level of tax compliance. This qualitative case study conducted interviews to directly obtain practitioners' data. The research was conducted at the East Jakarta DGT Regional Office, and Jakarta Pulogadung Primary Tax Service Office (KPPP). William Dunn’s evaluation framework was employed to gain more comprehensive results of effectiveness, efficiency, adequacy, equity, responsiveness, and appropriateness. This study concluded that CRM is not effective to raise the tax compliance rate. In addition, this study proposed several suggestions from the supervisory function executors regarding the future improvement and development of CRM, such as cleaner data. The results of this study can be used as a reference in developing CRM. In addition, other instruments and approaches should be considered to gain wider research insights.